Estilos de crianza parental y Trastornos de Conducta Alimentaria (TCA): una revisión aplicada - Chiappori Vizcarra, Rocio Maria (2023)
Eating Disorders (EDs) awaken maladaptive behaviors in relation to eating, damaging the patient's quality of life. This study aims to identify the relationship between parenting styles and EDs, specifically in Anorexia Nervosa (AN), Bulimia Nervosa (BN) and Binge Eating Disorder (BED), through and an applied review. Ten investigations were selected and revised according to PRISMA (Page et al., 2021) guidelines using databases of: Web of Science, Scopus and Scielo. The results show three types of relationships between parenting and the presence of ED symptoms. These were: predictive relation, positive and negative. Predictive relationships were predominant in the analyzed articles. A limitation when investigating is that due to the presence of the variable ED, most of the articles found had not taken a psychological perspective, hence they could not be used for this applied revision. In conclusion, parenting styles could present both a risk factor and preventative factor for the patient.